Analisis Kemampuan Literasi Numerasi Siswa Dalam Menyelesaikan Soal Cerita Materi Pecahan - Alif, Yusuf Emzi; Laili, Alik Mustafidal; Satria, Aditya Pringga (UNIB Press, 2024)
Numeracy literacy ability is a person's ability to solve something problems in the context of everyday life, involving knowledge and skills mathematics possessed to carry out reasoning in the form of analysis of information displayed so that the right decision can be obtained in solving it. Numeracy literacy covers a lot knowledge, not only in mathematics, but also related to other literacies. This research aims to describe students' numeracy literacy abilities class IV at SD Negeri 1 Moyoketen in solving story problems fractional material. This research was conducted at SD Negeri 1 Moyoketen. This research method uses a qualitative approach with this type of data descriptive. Data collection methods in this research are observation, interviews and documentation. Data analysis techniques used in this research is qualitative data analysis with a reduction flow data, data presentation, conclusion or verification. The results of the research show that students' numeracy literacy abilities in solving material story problems The fraction of class IV students at SD Negeri 1 Moyoketen is the average of the overall students have a sufficient level of ability as many as 11 students in percentage 55%. Students' numeracy literacy skills are demonstrated at a sufficient level. Students have basic mathematical skills, basic concepts related to story problems fraction material, and can solve mathematical problems effectively simple.